"The Seagull" as Heraldic "Mise en Abyme": Chekhov’s Philosophy of Melancholy - Božović, Ivana N.; Jovanović, Jelena M. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
The study of Chekhov’s philosophy of melancholy is conceived as a triptych. The first part, presented here, postulates the fundamental isochime of his oeuvre: the melancholic experience of the world. Chekhov’s aesthetics—understood both as a philosophy of art and as an artistic philosophy—are examined as an analytical category, a formative worldview, and a principle of authorial expression and action immanent to every creator. Drawing on Nikola Milošević’s typology from The Metaphysical Form of Miloš Crnjanski’s Work, which uses the “degree of transparency” of literary texts as its point of reference, we argue that Chekhov’s art belongs to the category of works that appear transparent while concealing profound meanings, thus requiring a subtle hermeneutic approach.Within the literary opus of this renowned Russian author, the melancholic experience of the world emerges as “a mirror reflected in a mirror, repeating itself endlessly,” a reflection that assumes a distinct and sublimated artistic form in The Seagull (1895). In this sense, the play becomes a heraldic mise en abyme (Fr. placement into the abyss), an internal reflection that permeating both both Chekhov’s dramatic and prose writings. The analysis focuses on three developmental stages and to a condensed interpretative prism outlining the contours of the tragic protagonist Konstantin Gavrilovich Treplyov. The seagull functions simultaneously as a symbol of anthemic weight, a metaphysical bond, and a radical gesture of renunciation of both self and the world. The study itself is structured according to an internal dramatic framework of four “acts,” mirroring the composition of The Seagull.The second part of the triptych will examine the active presence of the seagull symbol as an inaudible cry for meaning and Chekhov’s la grande tristezza (Dante), articulated within a distinct prose register. The third part will explore the mise en abyme within the visual discourse of Nikita Mikhalkov’s films: Unfinished Piece for Mechanical Piano (1977), Black Eyes (1987), and Burnt by the Sun (1994). In this way, the triptych becomes, in a certain sense, a “biography of a feeling,” an exploration of a “story within a story,” a “mirror reflected endlessly in another mirror”—a feeling both vital and ancient: melancholy.
Keywords: Chekhov; philosophy of melancholy; La mise en abyme; The Seagull; melancholic experience of the world